1968
DOI: 10.1002/jsfa.2740190406
|View full text |Cite
|
Sign up to set email alerts
|

Insecticides on single seeds treated with liquid dressings

Abstract: A method for determining insecticide on seeds treated with liquid formulations by extraction and gas chromatography of the extract was devised and used to estimate the amount of the insecticide on single seeds.Eight solvents were tested for their ability to extract aldrin from wheat seeds treated with a liquid formulation. Acetone-hexane was chosen for further investigation because in 24 hours at room temperature it extracted at least 95 % of the aldrin from treated seeds. This solvent almost quantitatively ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1970
1970
1976
1976

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Under certain conditions control is adequate but rarely complete. Damage has often been worse than expected due to late drilling, drought, prolonged winters or very heavy attacks or to inadequate retention of the powder or liquid dressing on the seed (Lord et al, 1967;Jeffs et al, 1968). Griffiths et al (1970) have greatly improved the accuracy of assessing insecticidal efficiency by measuring the amounts of active ingredient on seed samples and correlating this with subsequent control.…”
Section: Introductionmentioning
confidence: 99%
“…Under certain conditions control is adequate but rarely complete. Damage has often been worse than expected due to late drilling, drought, prolonged winters or very heavy attacks or to inadequate retention of the powder or liquid dressing on the seed (Lord et al, 1967;Jeffs et al, 1968). Griffiths et al (1970) have greatly improved the accuracy of assessing insecticidal efficiency by measuring the amounts of active ingredient on seed samples and correlating this with subsequent control.…”
Section: Introductionmentioning
confidence: 99%
“…Fungicide was added to the seeds when dry. The amounts of ethion on single seeds were estimated by the method of Jeffs et al (1968).…”
Section: Procedures For Special Formulationsmentioning
confidence: 99%
“…For comparison, some seeds were pre-treated with water (0-6 ml/100 g seed) before adding y-BHC, and others were treated with liquid parafiSn but received no insecticide. The amounts of y-BHC retained by sin^e seeds and by 5 g samples of seed were estimated by the method of Jeffs et al (1968).…”
Section: Procedures For Special Formulationsmentioning
confidence: 99%
“…Seed dressings of y-BHC have been approved since 1958 to protect winter wheat from attack by wheat bulb fly {Leptohylemyia coarctata (Fall.)). Recent analyses (Lord et al, 1967;Jeffs, Lord and Tuppen, 1968) showed that seeds often carry less insecticide than intended, so earlier results with y-BHC seed dressings are difficult to interpret because the amounts of active ingredient on the seeds were not necessarily those presumed. Six experiments were done, therefore, to get information about the effects on wheat and insecticidal efliciency of known amounts of y-BHC checked by gas liquid chromatography (G.L.C.).…”
Section: Introductionmentioning
confidence: 99%